Structural, Thermal, Physical, Mechanical, and Barrier Properties of Chitosan Films with the Addition of Xanthan Gum. Issue 3 (20th February 2017) - de Morais Lima, Maria; Carneiro, Lucia Cesar; Bianchini, Daniela; Dias, Alvaro Renato Guerra; Zavareze, Elessandra da Rosa; Prentice, Carlos; Moreira, Angelita da Silveira
Abstract: Films based on chitosan and xanthan gum were prepared using casting technique aiming to investigate the potential of these polymers as packaging materials. Six formulations of films were studied varying the proportion of chitosan and xanthan gum: 100:0 (chitosan:xanthan gum, w/w, C100XG0 film); 90:10 (chitosan:xanthan gum, w/w, C90XG10 film); 80:20 (chitosan:xanthan gum, w/w, C80XG20 film); 70:30 (chitosan:xanthan gum, w/w, C70XG30 film); 60:40 (chitosan:xanthan gum, w/w, C60XG40 film); and 50:50 (chitosan:xanthan gum, w/w, C50XG50 film). The total quantity of solids (chitosan and xanthan gum) in the filmogenic solution was 1.5 g per 100 mL of aqueous solution for all treatments, according to the proportion of each polymer. The films were evaluated by their functional groups, structural, thermal, morphological, physical, mechanical, and barrier properties. All films have presented endothermic peaks in the range of 122 to 175 °C and broad exothermic peaks above 200 °C, which were assigned to the melting temperature and thermal decomposition, respectively. These results demonstrated that films with xanthan gum have the highest T m and Δm H . The films containing higher content of xanthan gum show also the highest tensile strength and the lowest elongation. Xanthan gum addition did not affect the water vapor permeability, solubility, and moisture of films. This set of data suggests the formation of chitosan–xanthan complexes in the films.